1982
DOI: 10.3109/00365528209182235
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Occurrence of Abdominal Pain and Endoscopic Findings in Patients with Gastric and Duodenal Ulcer Disease

Abstract: Fifty patients with peptic ulcer disease were followed up to 1 to 5 years. Panendoscopy was repeated on the average of 5.6 times a year, also in patients who were actually well. The pattern of changes during on calendar year was a substantial comparative unit. The incidence and intensity of pain, erosions, and ulcers were registered in yearly charts, and the results were calculated per month from 100 yearly cycles. Pain appeared to be the most frequent symptom, being reported in 50% to 100% of visits in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The reason why some ulcers are asymptomatic is unknown. In controlled trials, both asymptomatic duodenal ulcers and gastric ulcers have been found in a substantial proportion of cases (44,45). We found that eight subjects (19.5 percent of all ulcer patients and 0.8 percent of the study population) had asymptomatic PUD.…”
Section: Discussionmentioning
confidence: 67%
“…The reason why some ulcers are asymptomatic is unknown. In controlled trials, both asymptomatic duodenal ulcers and gastric ulcers have been found in a substantial proportion of cases (44,45). We found that eight subjects (19.5 percent of all ulcer patients and 0.8 percent of the study population) had asymptomatic PUD.…”
Section: Discussionmentioning
confidence: 67%
“…Although some consider erosive duodenitis to be a separate entity, most consider it to be a variety of duodenal ulcer 19 , . 20 In the intention‐to‐treat analysis, losses during follow‐up, are considered as failures.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy is the most sensitive diagnostic test for peptic ulcers. The main role of endoscopy in patients with uncomplicated Peptic Ulcer disease is to confirm the diagnosis, identify lesions too small to be detected by radiographic examination and to rule out malignancy by performing endoscopic biopsy 7 .…”
Section: Introductionmentioning
confidence: 99%